2002
DOI: 10.1039/b205248m
|View full text |Cite
|
Sign up to set email alerts
|

Direct formation of hydrogen peroxide from H2/O2 using a gold catalyst

Abstract: Supported Au catalysts are very selective for the direct formation of hydrogen peroxide from H2/O2 mixtures at 2 degrees C; the rate of H2O2 synthesis is markedly increased if Au-Pd alloy nanoparticles are generated by the addition of Pd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
415
0
15

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 505 publications
(441 citation statements)
references
References 6 publications
11
415
0
15
Order By: Relevance
“…Supported Au catalysts have been investigated for the oxidation of propene to propene oxide using O2/H2 mixtures (39), and it is considered that a surface hydroperoxy species may be formed as the oxidant. We have found that supported Au catalysts can be very effective for the synthesis of hydrogen peroxide (40,41) and, furthermore, the rate of hydrogen peroxide formation can be significantly enhanced by the use of a supported Au/Pd alloy.…”
Section: Production Of Hydrogen Peroxide By the Oxidation Of Moleculamentioning
confidence: 97%
“…Supported Au catalysts have been investigated for the oxidation of propene to propene oxide using O2/H2 mixtures (39), and it is considered that a surface hydroperoxy species may be formed as the oxidant. We have found that supported Au catalysts can be very effective for the synthesis of hydrogen peroxide (40,41) and, furthermore, the rate of hydrogen peroxide formation can be significantly enhanced by the use of a supported Au/Pd alloy.…”
Section: Production Of Hydrogen Peroxide By the Oxidation Of Moleculamentioning
confidence: 97%
“…Transportation from point of manufacture to point of use is expensive and there is a definite market need to develop a safe, modular process that can be operated cost effectively at the point of use. There is evidence emerging in the literature and patent applications that gold-based catalysts might be applied effectively for this purpose (19,20). There is an interesting link in this potential application to the gold mining industry where peroxide is used to destroy cyanide waste.…”
Section: Chemical Processingmentioning
confidence: 99%
“…Gold metal catalysis has already been successfully used in gas phase reactions like the low temperature oxidation of CO (2,3), the acetylene hydrochlorination (4), the water-gas shift (5) and the epoxidation of propylene (6). Examples of liquid phase metallic gold catalyzed reactions are redox reactions such as the oxidation of alcohols and aldehydes (7)(8)(9), the hydrogenation of unsaturated ketones to allylic alcohols (10) and the synthesis of H 2 O 2 (11). Particularly in the liquid phase oxidation of 1,2-diols like 1,2-ethanediol and 1,2-propanediol, Prati and Rossi showed that gold is a suitable alternative for platinum group catalysts, because the surface of Au is not readily overoxidized and is hardly sensitive to chemical poisoning by acid adsorption (12).…”
Section: Introductionmentioning
confidence: 99%